2020
DOI: 10.1038/s41598-020-63382-0
|View full text |Cite|
|
Sign up to set email alerts
|

Dimethyl disulfide exerts antifungal activity against Sclerotinia minor by damaging its membrane and induces systemic resistance in host plants

Abstract: Microbial volatile compounds (MVCs) significantly influence the growth of plants and phytopathogens. However, the practical application of MVCs at the field level is limited by the fact that the concentrations at which these compounds antagonize the pathogens are often toxic for the plants. In this study, we investigated the effect of dimethyl disulfide (DMDS), one of the MVCs produced by microorganisms, on the fitness of tomato plants and its fungicidal potential against a fungal phytopathogen, Sclerotinia mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 57 publications
(111 reference statements)
0
38
0
1
Order By: Relevance
“…Although less effective than AITC, dimethyl sulfide has been known to cause growth reductions for several plant pathogens. [80][81][82] Other ITCs such as benzyl ITC or phenylethyl ITC could have been formed as well, although they were not found in the headspace analysis. Only traces of butyl ITC were found in B. juncea cvs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less effective than AITC, dimethyl sulfide has been known to cause growth reductions for several plant pathogens. [80][81][82] Other ITCs such as benzyl ITC or phenylethyl ITC could have been formed as well, although they were not found in the headspace analysis. Only traces of butyl ITC were found in B. juncea cvs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, dimethyl sulfide was found in the qualitative headspace analysis of all oilseed radish cultivars and some white mustard cultivars (see Supporting information, Table S4). Although less effective than AITC, dimethyl sulfide has been known to cause growth reductions for several plant pathogens 80–82 . Other ITCs such as benzyl ITC or phenylethyl ITC could have been formed as well, although they were not found in the headspace analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Similar specificity in VOC induction was observed by Naznin and colleagues (2014), who demonstrated M‐cresol, the dominant VOC from Cladosporium , induced salicylic acid and jasmonic acid signalling pathways in A. thaliana when challenge inoculated with Pseudomonas syringae , whereas methyl benzoate, the dominant VOC from Ampleomyces , induced jasmonic acid signalling with partial salicylic acid signals. Expression of genes involved in salicylic acid signalling is also induced in tomato plants exposed to dimethyl disulfide, enhancing defence against Sclerotinia minor (Tyagi et al ., 2020). Interestingly, as well as directly suppressing growth of Ralstonia solanacearum , benzaldehyde, 1,2‐benzisothiazol‐3(2H)‐one and 1,3‐butadiene elicited induced systemic resistance in tobacco, through induction in the transcriptional expression of defence related genes, demonstrating potential multi‐functional roles of mVOCs (Tahir et al ., 2017a).…”
Section: Role Of Volatiles In Induced Resistancementioning
confidence: 99%
“…For example, inhibitory mVOCs produced by Streptomyces yanglinensis 3–10 against Aspergillus were tested to determine their effects on plant development and showed that VOCs did not inhibit peanut seedling germination, suggesting promise for use under field conditions (Lyu et al ., 2020). The modes of action of VOCs in the suppression of target pathogens (Dalilla et al ., 2015; Cho et al ., 2017; Tahir et al ., 2017a; Xie et al ., 2018; Yang et al ., 2019; Ojaghian et al ., 2019), enhanced disease resistance of plants (Ryu et al ., 2004; Lee et al ., 2012; Song and Ryu, 2013; Tahir et al ., 2017a; Tahir et al ., 2017b; Song et al ., 2019b; Tyagi et al ., 2020) and plant growth promotion (Ryu et al ., 2003; Garnica‐Vergara et al ., 2016; Lee et al ., 2019; Tyagi et al ., 2019) are receiving increasing attention, future research priority should focus on understanding the mode of action of biologically active VOCs on target plants and pathogens. Whilst investigation of the efficacy of VOCs under field conditions has demonstrated promise, a wider range of VOCs require testing at this scale.…”
Section: Conclusion and Future Outlookmentioning
confidence: 99%
“…A controlled mechanism of the plant holobiont to maintain microbial activity during drought recovery also stems from root exudates that can trigger more soil respiration (priming of soil carbon), thus facilitating regrowth through stimulating microbial activity in the rhizosphere (Vries et al ., 2019). Similarly, microbial VOCs like 2,3‐butanediol and DMDS can induce abiotic stress tolerance consequently preventing the suppression of plant growth and reduction in crop yields (Ryu et al ., 2004; Tyagi et al ., 2020). The same compound, 2,3‐butanediol was shown to induce drought tolerance by stimulating the plant production of hydrogen peroxide (H 2 O 2 ) and nitric oxide (NO) (Cho et al ., 2013).…”
Section: Current Trends: Infochemicals Across Plant and Seaweed Holobmentioning
confidence: 99%